Wearable Cardioverter–Defibrillators following Cardiac Surgery—A Single-Center Experience - Heimeshoff, Jan; Merz, Constanze; Ricklefs, Marcel; Kirchhoff, Felix; Haverich, Axel; Bara, Christoph; Kühn, Christian (The Thoracic and Cardiovascular Surgeon, 2019)
Background A wearable cardioverter–defibrillator (WCD) can terminate ventricular fibrillation and ventricular tachycardias via electrical shock and thus give transient protection from sudden cardiac death. We investigated its role after cardiac surgery.Methods We retrospectively analyzed all patients who were discharged with a WCD from cardiac surgery department. The WCD was prescribed for patients with a left ventricular ejection fraction (LVEF) of ≤35% or an explanted implantable cardioverter–defibrillator (ICD).Results A total of 100 patients were included in this study, the majority (n = 59) had received coronary artery bypass graft surgery. The median wearing time of a WCD patient was 23.5 hours per day. LVEF was 28.9 ± 8% after surgery and improved in the follow-up to 36.7 ± 11% (p < 0.001). Three patients were successfully defibrillated. Ten patients experienced ventricular tachycardias. No inappropriate shocks were given. An ICD was implanted in 25 patients after the WCD wearing period.Conclusion Ventricular arrhythmias occurred in 13% of the investigated patients. LVEF improved significantly after 3 months, and thus a permanent ICD implantation was avoided in several cases. Sternotomy did not impair wearing time of the WCD. A WCD can effectively protect patients against ventricular tachyarrhythmias after cardiac surgery.
Keywords: Arrhythmia Therapy; surgical; heart failure; postoperative mortality